Quantum dot: magic nanoparticle for imaging, detection and targeting - Ghasemi, Y.; Peymani, P.; Afifi, S. (Acta Biomedica Atenei Parmensis, 2009)
Quantum dots (QDs) are one of the nanoparticles that use in Imaging, Detection and Targeting. Quantum dots are nanometer-size luminescent semiconductor crystals and have unique chemical and physical properties due to their size and their highly compact structure. They emit different wavelengths over a broad range of the light spectrum from visible to infrared, depending on their size and chemical composition. Eventual use of quantum dots to dramatically improve clinical diagnostic tests for the early detection of cancer.  The use of quantum dots heralds a revolution in biological imaging. The current and widely used organic fluorophores have two shortcomings associated with their fluorescence. Signals from the labeled molecules can be obscured by cell autofluorescence, occurring in the visible spectrum and by photobleaching which seriously limits observation time. Colloidal quantum dots are bright, photostable fluorophores of a few nanometers in diameter. Because their size approximates that of individual biomolecules, water-soluble quantum dot complex have been used to target and image tumor cells. Despite their advantages the best materials for quantum dots; cadmium sulfide, CdS and cadmium selenide, CdSe can be highly toxic. While enhancing the biocompatibility of this nanoparticle various encapsulation techniques have also aided in their water-dispersibility and functionalization. QDs were introduced to cell biology as alternative fluorescent probes in recent years. Traditional fluorophores, e.g. organic dyes and fluorescent proteins are limited by their narrow absorption range, broad emission spectra and short fluorescent lifetime.